Vitamin C may have similar beneficial effects to Gemfibrozil on serum high-density lipoprotein-cholesterol in type 2 diabetic patients - Mansour Siavash; Masoud Amini (Wolters Kluwer Medknow Publications, 2014)
Objective: Type 2 diabetes mellitus (DM-T2) is commonly associated with increased triglycerides (TG), low-density lipoprotein cholesterol (LDL-C) and low high-density lipoprotein cholesterol (HDL-C) levels. Fibrates like gemfibrozil are frequently used in diabetic patients to decrease TG and increase HDL-C levels. We compared the efficacy of Vitamin C, an antioxidant vitamin, with gemfibrozil on serum HDL-C in diabetic patients. Methods: Type 2 diabetic patients, referred to our out-patient clinic were randomly divided into three groups. After 1 month of lifestyle and diet modifications, groups A, B, and C were prescribed 1000 mg Vitamin C, 600 mg gemfibrozil and combination of both, respectively. Before the study initiation and after 6 th week of drug prescription, the blood samples were taken and analyzed for total cholesterol (Total-C), HDL-C, TG, fasting blood sugar (FBS), and hemoglobin A1c (HbA1c) levels. Findings: Sixty-seven patients entered, and 50 patients (18 male, 32 female) finished the study. Overall, serum HDL-C increased significantly from 39.8 to 45.2 mg/dL in the participants (P = 0.001). HDL-C increased 6.3, 4.4 and 5.0 mg/dL in groups A, B and C, respectively (related significances were 0.017, 0.022 and 0.033, respectively). Significant decrease of serum TG and Total-C occurred in gemfibrozil and combination groups, but not in Vitamin C group. Changes in serum HDL-C between three groups were not significant (P = 0.963). We found a significant decrease in TG and Total-C in the groups B and C (P < 0.05), but no significant changes of TG, Total-C, LDL-C, FBS and HbA1c in group A (P > 0.05). Conclusion: The results demonstrated that Vitamin C may have beneficial effects on HDL-C in diabetic patients without significant effects on plasma glucose or other lipid parameters; however, its role for the treatment of low HDL-C patients should be evaluated in larger studies.